A study on the budget announcement and its effects on the industrial sector of Kuala Lumpur Stock Exchange / Abdul Hadi Zulkafli - Zulkafli, Abdul Hadi (1997)
This study attempts to explore the impact of changes in our annual budget with particular on industrial sector of Kuala Lumptfr Stock Exchange.Five companies that meet the sampling requirements were included in the sample of seven years period (1991-1997). The stock performance is based on daily price of selected industrial counters, daily industrial volume and daily industrial index (30 days before and 30 days after the budget announcement).The budget variable is represented by corporate tax, income tax and EPF. Using the regression and correlation analysis, an alternate hypothesis is developed.The hypothesis states that price, volume and index are dependent on those budget variables.Computed by a statistical package, SPSS, the coefficient of correlation , coefficient of determination and t~statistic test are used to quantify the relationship.